Industrial training report: Selayang Municipal Council / Nik Irsaal Nik Lah - Nik Lah, Nik Irsaal (Perpustakaan Tengku Anis, 2017)
The Industrial Training report is based on the period from 1st February 2017 to 30th June 2017. The Industrial Training has taken place at headquarters Selayang Municipal Council or also known as Majlis Perbandaran Selayang (MPS). The trainee has been placed in Information Technology Department (IT Unit). In this report, it was highlighted about the training activities, experiences, skills and challenges that the trainee has been encountered All training activities and special project are recorded in this Industrial Training report. The trainee has been assigned to developed 1 system which is from manual form to system named E-filling which demanding the ability of the trainee to developed 1 system that can be used by MPS staff